Kedudukan Anak Angkat dalam Pewarisan Menurut Hukum Adat Bali (Studi Kasus Desa Adat Gunaksa) - I Nengah Sunaradana; I Wayan Rideng; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
The position of adopted children in inheritance based on Balinese customary law has indeed been determined to provide rights for adopted children. This research aimed to examine the customary procedures for adopting children according to Balinese Customary Law and the position of adopted children related to the inheritance of their parents (biological and adoptive). This research uses empirical legal methods with juridical and sociological approaches. The sources of legal materials used are primary and secondary. The legal materials in this research were collected using two data collection techniques, namely interview and documentation techniques. Then, the sample selection in this research was carried out by using purposive sampling technique, then it was analyzed systematically. The results of the research indicates that the position of an adopted child is the same as that of a biological child - acting as the legal heir and successor - if he comes from a large family of adoptive parents. The inheritance of the adoptive parents' inheritance will be fully handed over to the adopted son, including the family heirloom of his adoptive parents. Meanwhile, the position of adopted children is only limited to the inheritor of wealthy assets if they come from outside the extended family of the adopted parent - inheritance to the legal owner. In this condition, if the adoptive parents die, then the family relationship between the adopted child and the adoptive parents is severed.